Flexible Work Culture Transformation in Enhancing Employee Well-Being During the Sustainable Global Digital Era - Komang Meydiana Hutama Putri (Mandalika Institute, 2026)
The rapid advancement of digital technologies has accelerated the transformation of flexible work culture, making it an essential strategy for enhancing employee well-being in sustainable organizations. This study aims to analyze how flexible work culture contributes to employee well-being during the sustainable global digital era. The research employs a qualitative library research approach using content analysis to synthesize information from scholarly books, peer-reviewed journals, research reports, and other relevant academic sources. The analysis is guided by the Job Demands–Resources (JD-R) Theory to examine the relationship between organizational flexibility, digital transformation, and employee well-being. The findings indicate that flexible work culture positively influences employee well-being by increasing autonomy, work-life balance, job satisfaction, engagement, and organizational commitment when supported by adequate organizational resources. However, digital transformation may also generate challenges such as technostress, digital fatigue, and blurred work-life boundaries. Therefore, organizations should integrate flexible work culture with supportive leadership, digital capability, and sustainable human resource management to achieve long-term organizational resilience and employee well-being.